What can global perspectives contribute to curriculum development in social policy? - Irving, Zoe; Young, Pat; Yeates, Nicola (2005)
This article argues the case for the integration of a global perspective within social policy as a means of enriching teaching and learning methods and experiences. We review the various ways in which such a perspective is currently integrated into social policy degrees and address some of the opportunities and challenges for teaching and learning that it involves. We consider current thinking on curriculum development, which, we contend, can facilitate the integration of a global perspective into social policy analysis and the alignment of the various factors influencing student learning. - Reproduced.
Keywords: Social policy; Curriculum development